2005
DOI: 10.1097/01.rhu.0000164820.46979.52
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of the Clinical Manifestations and Outcomes in Puerto Ricans with Idiopathic Inflammatory Myopathies

Abstract: Puerto Ricans with IIM in this survey showed a low presence of visceral involvement, high remission rate, and low mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
8
1
2
Order By: Relevance
“…This retrospective study of 188 IIM patients is more representative of overall IIM patients. The overall mortality in our study was 17%, similar to other published series [11,18,31,37], but lower than that Troyanov Y reported [7]. Importantly, our results indicated that cumulative survival rate was better than other series reported over 15 years (Table 5) [7,9-12,15,29,32,33].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This retrospective study of 188 IIM patients is more representative of overall IIM patients. The overall mortality in our study was 17%, similar to other published series [11,18,31,37], but lower than that Troyanov Y reported [7]. Importantly, our results indicated that cumulative survival rate was better than other series reported over 15 years (Table 5) [7,9-12,15,29,32,33].…”
Section: Discussionsupporting
confidence: 86%
“…There is still some debate on the relationship between skin ulcer and outcome. Several studies showed that skin ulcer was not associated with the risk of mortality in Chinese Han patients and Caucasian patients [8-10,13,15,17,20,33,32,37]. …”
Section: Discussionmentioning
confidence: 99%
“…[1315182123] CPK was elevated in 85% of cases in the current study, which was higher than that described by DeVere et al . [13] who found CPK elevation in 64% of cases.…”
Section: Discussioncontrasting
confidence: 86%
“…One-fourth of our patients had bulbar muscle weakness at the time of initial evaluation, whereas it was only 10% in a study published by Rios et al . [21]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation